2003
DOI: 10.1086/345744
|View full text |Cite
|
Sign up to set email alerts
|

Linezolid for the Treatment of Multidrug‐Resistant, Gram‐Positive Infections: Experience from a Compassionate‐Use Program

Abstract: Linezolid was provided for treatment of multidrug-resistant, gram-positive infections through a compassionate-use program. Patients (n=796) received 600 mg of linezolid intravenously or orally every 12 h (828 treatment courses). Bacteremia was present in 46% of infections, endocarditis was present in 10.6%, and line-related infections were present in 31.1%. Other infections included intraabdominal infections (15.1%), complicated skin and skin-structure infections (13.3%), and osteomyelitis (10.7%). Causative p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
197
3
6

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 382 publications
(216 citation statements)
references
References 23 publications
7
197
3
6
Order By: Relevance
“…[12,13] Prolonged use outside the recommended safe period is often undertaken but has previously been associated with optic and peripheral neuropathies. [2,[4][5][6][7] In this case the patient had already been on linezolid 600 mg once daily for fourteen months before she developed symptoms due to its toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…[12,13] Prolonged use outside the recommended safe period is often undertaken but has previously been associated with optic and peripheral neuropathies. [2,[4][5][6][7] In this case the patient had already been on linezolid 600 mg once daily for fourteen months before she developed symptoms due to its toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…6,9 Recent research supports use of alternative agents for MRSA bacteremia, but the use of these agents is often reserved for patients who cannot tolerate vancomycin, have persistent bacteremia during treatment with vancomycin, or have MRSA infections for which vancomycin MICs are elevated. 6,9,22,23,25,26,38 Daptomycin has the most data to support its use as an alternative agent in MRSA bacteremia in both the IDSA 2009 CLABSI and 2011 MRSA guidelines. Linezolid should be reserved for salvage therapy.…”
Section: Discussionmentioning
confidence: 99%
“…6 Available data do support use of linezolid as an alternative agent in MRSA bacteremia. The effectiveness of linezolid as definitive treatment for MRSA bacteremia was shown in an observational compassionate use program 25 as well as a pooled analysis 26 of data from 5 randomized controlled trials that showed similar clinical cure rates for vancomycin and linezolid (46% vs 56%; odds ratio, 1.47; 95% CI, 0.50-4.31). Additionally, findings of an open-label randomized controlled study 27 published in 2009 indicated that linezolid and vancomycin treatment of MRSA CLABSIs had similar successful clinical outcomes (79% vs 76%; 95% CI, -21 to 27).…”
Section: Definitionmentioning
confidence: 99%
“…The following antibacterial agents have been approved during the last five years: quinupristin/dalfopristin, [29][30][31][32] linezolid, 33,34 daptomycin, [35][36][37] and tigecycline. 38,39 Novel lipoglycopeptide agents under study include dalbavancin, 40 telavancin, and oritavancin.…”
Section: Novel Antibacterial Agents With Enhanced Activity Against Rementioning
confidence: 99%